The wonder boy of Whistle Stop : a novel - Flagg, Fannie (Random House, 2020)
"Bud Threadgoode grew up in the bustling little railroad town of Whistle Stop, Alabama, with his mother Ruth, church going and proper, and the fun-loving hell-raiser, his Aunt Idgie. Together they ran the town's popular Whistle Stop Café, known far and wide for its famous 'Fried Green Tomatoes.' And as Bud often said of his childhood, 'How lucky can you get?' But sadly, the railroad yards began to shut down and the town became a ghost town, with nothing left but boarded-up buildings and memories of a happier time. Then one day, Bud decides to take one last trip, just to see where his beloved Whistle Stop used to be. In so doing, he discovers new surprises about Idgie's life and about other beloved Fried Green Tomatoes characters, and about the town itself. He also sets off a series of events, both touching and inspiring, which change his life and the lives of his daughter and others. Could these events all be just coincidences? Or something else? And can you go home again?"--